2018
DOI: 10.1097/md.0000000000009311
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound versus auscultation in determining the position of double-lumen tube

Abstract: This study was designed to assess the accuracy of point-of-care ultrasound in determining the position of double-lumen tubes (DLTs).A total of 103 patients who required DLT intubation were enrolled into the study. After DLTs were tracheal intubated in the supine position, an auscultation researcher and ultrasound researcher were sequentially invited in the operating room to conduct their evaluation of the DLT. After the end of their evaluation, fiberscope researchers (FRs) were invited in the operating room to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…POCUS showed statistically significant higher diagnostic accuracy than auscultation. [4] Despite this evidence from the adult population, there is only one anecdotal case report in the pediatric population. [6]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POCUS showed statistically significant higher diagnostic accuracy than auscultation. [4] Despite this evidence from the adult population, there is only one anecdotal case report in the pediatric population. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Although POCUS in all of the previously mentioned studies except one was performed in the supine position, we performed the study in both the supine and lateral decubitus positions. [4] As the position of the ETT may change after the patient is placed in the lateral decubitus position, a repeat study may be indicated once the patient is positioned. We were able to evaluate easily the nondependent lung by ultrasound after positioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies evaluating lung ultrasound were performed in patients who were scheduled for elective surgery with limited intrinsic lung disease. [3][4][5][6] Pulmonary parenchymal with consolidation or atelectasis may impede lung ultrasound as lung sliding is observed only in ventilated areas. Therefore, even if two-lung ventilation is performed, Figure 3 Bar code sign in an adult.…”
Section: Limitations Of Lung Ultrasonographymentioning
confidence: 99%
“…2 Similar results have been reported when using a double lumen endotracheal tube for OLV. [3][4][5][6] To date, there are a limited number of case reports regarding the use of lung ultrasound in children and no prospective clinical trials. There is increasing clinical use of point-of-care ultrasound (POCUS) to identify effective lung separation thereby eliminating the need for bronchoscopy and limiting inaccuracies with auscultation.…”
Section: Introductionmentioning
confidence: 99%